Analysis of an industrial operation of B5 diesel fuel supply and development of an optimization solution - Azálgara Bedoya, Mauricio (2019)
Within the framework of the Las Bambas mining megaproject, the industrial operation of B5 diesel fuel supply was regulated by contract CB02912, in which the parties involved were Xstrata Copper and Petróleos del Perú. In the industrial operation, it was estimated that up to 8 % of goods were not delivered between years 2012 and 2013, resulting in untimely fuel shortages in the customer’s facilities, noncompliance with diesel fuel cleanliness standards, among others. The present research establishes the guidelines for the comprehensive management of the contract.